The Influence of Corporate Social Responsibility, Profitability, and Company Size on Firm Value in Primary Goods Retail Companies Listed on the Indonesia Stock Exchange - Nadia Naman; Bambang Sutrisno (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR), profitability, and company size on firm value in primary goods retail trading companies listed on the Indonesia Stock Exchange (IDX). The study is conducted to obtain empirical evidence about the factors influencing firm value as well as to explain the differences in previous research findings regarding the relationships among these variables. This research uses a quantitative approach with an associative research type. The data used are secondary data in the form of annual financial statements of companies obtained from the Indonesia Stock Exchange. The sampling technique employed is purposive sampling, resulting in a sample of 6 (six) companies. The data analysis method used is panel data regression assisted by Stata 17 software. The research results indicate that, partially, Corporate Social Responsibility (CSR) has a positive and significant effect on firm value, whereas profitability has a negative and significant effect on firm value. Meanwhile, firm size has a negative and insignificant effect on firm value. Simultaneously, Corporate Social Responsibility (CSR), profitability, and firm size have a significant effect on firm value in primary goods retail trading companies listed on the Indonesia Stock Exchange.